Efficacy and Safety of Transarterial Chemoembolization in Elderly Patients of Advanced Hepatocellular Carcinoma With Portal Vein Tumor Thrombus: A Retrospective Study - Tang, Qinghe; Huang, Wei; Liang, Jun; Xue, Junli (Frontiers in Oncology, 2021)
Objective The aim of the current study was to evaluate the safety and efficacy of transcatheter arterial chemoembolization (TACE) in elderly patients diagnosed as advanced hepatocellular carcinoma (HCC) accompanied with different types of portal vein tumor thrombosis (PVTT). Methods Elderly HCC patients aged 70-year-old and above from January 2015 to December 2019 were included in this retrospective study. Efficacy data including OS, PFS, DCR, and ORR and safety data were collected in the indicated groups. Outcomes of HCC patients in the TACE group were compared with those patients in the best supportive care (BSC) group. Subgroup analyses were also conducted in the patients with different types of PVTT. Results Among 245 elderly HCC patients, 124 were enrolled in this study. Out of these, 50.0% (n=62) underwent BSC treatment while 50.0% (n=62) underwent TACE. There were no major differences in the baseline characteristics of the two treatment groups. TACE treatment was associated with better median OS compared with BSC alone (11.30 m vs. 7.80 m; P<0.001). Subgroup analyses showed that patients with type I and type II PVTT could benefit from TACE compared with BSC, based on that OS was 14.30 m vs. 7.80 m (P=0.007) and 13.00 m vs. 8.00 m (P=0.002), respectively. The DCR in the TACE group was 62.90%, and 17.74% in the BSC group (p<0.001). The proportion of ORR in TACE group was 35.48%, while 0.00% in the BSC group (p<0.001). Multivariable analyses showed that patients undergoing TACE treatment had 52% lower odds of mortality compared with patients undergoing BSC treatment (HR: 0.48; 95%CI: 0.32-0.72). Similarly, the media PFS was improved following TACE treatment (7.50 m vs. 4.00 m; P<0.001). TACE could significantly prolong the PFS in both type I and type II PVTT subgroups, without greatly significant improvement in type III PVTT patients (4.50 m vs. 2.70 m; P=0.103). Type III PVTT patients in the TACE group had more AEs than type I and type II PVTT patients. According to multivariable analyses, PVTT types (type III vs. type I-II) (HR: 2.18; 95%CI: 1.29-3.70; P=0.004), tumor diameter (>5 cm vs. ≤5 cm) (HR: 1.94; 95%CI: 1.28-2.93; P=0.002), and treatment (TACE vs. BSC) (HR: 0.48; 95%CI: 0.32-0.72; P<0.001) were independent indicators of overall survival. Conclusions In elderly advanced HCC patients with PVTT, palliative TACE treatment can be an accessible effective measure to improve the OS and PFS for both type I and type II PVTT patients.